2022
DOI: 10.1021/acs.jmedchem.1c01870
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Membranes as Actionable Targets for Lipid-Centric Therapy in Tuberculosis

Abstract: Infectious diseases remain significant health concerns worldwide, and resistance is particularly common in patients with tuberculosis caused by Mycobacterium tuberculosis. The development of anti-infectives with novel modes of action may help overcome resistance. In this regard, membrane-active agents, which modulate membrane components essential for the survival of pathogens, present attractive antimicrobial agents. Key advantages of membrane-active compounds include their ability to target slow-growing or do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 195 publications
0
17
0
Order By: Relevance
“…, inducing permeabilization and upregulating a stress reporter promoter), compound 55 directly inhibits MmpL3 without affecting the membrane charge or proton gradients . Membrane-targeted antibacterial or antitubercular small molecules have been recently reviewed …”
Section: Preclinical Promisesmentioning
confidence: 99%
See 1 more Smart Citation
“…, inducing permeabilization and upregulating a stress reporter promoter), compound 55 directly inhibits MmpL3 without affecting the membrane charge or proton gradients . Membrane-targeted antibacterial or antitubercular small molecules have been recently reviewed …”
Section: Preclinical Promisesmentioning
confidence: 99%
“…179 Membrane-targeted antibacterial or antitubercular small molecules have been recently reviewed. 180 Another well-known class of MmpL3 inhibitors is indolecarboxamides, including NITD-304 (56) and NITD-349 (57) (Figure 6), which were disclosed by Novartis as preclinical candidates in 2013 and provided to the TB Alliance in the following year. 92, 134 Stec et al reported the new analogue 58 (Figure 6), following optimization of their earlier cyclooctylamide lead.…”
Section: Compounds Targeting Cell Wallmentioning
confidence: 99%
“…It is thus not surprising that various inhibitors of specific processes of the cell wall biosynthesis [ 8 , 9 , 10 , 11 ] have long been established as a major group of antitubercular drugs. Moreover, the approaches aiming to directly target and modulate the mycobacterial membranes are currently seen as very promising [ 12 ]. Among the cell envelope layers, perhaps the most important protective role belongs to the wax-like outer membrane [ 7 , 8 , 13 ] that has high strength and extremely low permeability for external molecules (especially the relatively hydrophilic ones, including some antibiotics [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“… 28 Mycobacterial fatty coats are the preferential target for anti-tuberculous drugs. 61 Most bioactive lipids of M. tuberculosis are not addressable in aqueous milieux for biological interactions to occur, but only through nanotechnology approaches. …”
Section: Fat: the Molecular Key Feature In The Tubercle Bacillusmentioning
confidence: 99%